“There Are No Women and They All Play Mercy”: Understanding and Explaining (the Lack of) Women’s Presence in Esports and Competitive Gaming - Ruotsalainen Maria; Friman Usva (My University, 2022)
In this paper, we explore women’s participation in esports and competitive gaming. We will analyze two different types of research material: online questionnaire responses by women explaining their reluctance to participate in esports, and online forum discussions regarding women’s participation in competitive Overwatch. We will examine the ways in which women’s participation – its conditions, limits and possibilities – are constructed in the discussions concerning women gamers, how women are negotiating their participation in their own words, and in what ways gender may affect these processes. Our findings support those made in previous studies concerning esports and competitive gaming as fields dominated by toxic meritocracy and hegemonic (geek) masculinity, and based on our analysis, women’s room for participation in competitive gaming is still extremely limited, both in terms of presence and ways of participation.
DiGRA Nordic '18: Proceedings of 2018 International DiGRA Nordic Conference